2000
DOI: 10.1159/000024442
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Paramyosin, a New Allergen of <i>Anisakis simplex</i>

Abstract: Background: Anisakis simplex is a fish parasite that, when accidentally ingested by humans, may cause allergic reactions in sensitized individuals. The main objectives of our study were to: (1) construct a cDNA expression library of A. simplex; (2) identify clones producing specific IgE binding protein antigens, and (3) produce and purify the protein/s codified by the isolated clones produced in Escherichia coli. Methods: An expression cDNA library from the third stage larvae (L3) of A. simplex was constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…A major allergen of another nematode, Anisakis simplex, Ani s 2, is also paramyosin. 20) Although no experimental data suggested that paramyosin is important as a cross-reactive antigen between Ascaris and HDM antigens until recently, a very recent report states that the recombinant Blo t 11 fusion protein showed IgE reactivity in 80% of allergic subjects and 46% of ascariasis subjects, 15) suggesting that a potential role of paramyosin as an important crossreactive allergen in HDMs and Al.…”
Section: Discussionmentioning
confidence: 99%
“…A major allergen of another nematode, Anisakis simplex, Ani s 2, is also paramyosin. 20) Although no experimental data suggested that paramyosin is important as a cross-reactive antigen between Ascaris and HDM antigens until recently, a very recent report states that the recombinant Blo t 11 fusion protein showed IgE reactivity in 80% of allergic subjects and 46% of ascariasis subjects, 15) suggesting that a potential role of paramyosin as an important crossreactive allergen in HDMs and Al.…”
Section: Discussionmentioning
confidence: 99%
“…Ani s 2 and Ani s 3 are the two somatic allergens described so far (22,23,108,212). They are paramyosin and tropomyosin proteins, respectively, and are similar to the paramyosins and tropomyosins of other species (reviewed by Weiler [279]).…”
Section: Anisakis Allergensmentioning
confidence: 99%
“…Ani s 1 (21 kDa) [10] belongs to the serin-type endopeptidase inhibitor family since it contains a Kunitz domain. Ani s 2 (paramyosin, 100 kDa) [11] and Ani s 3 (tropomyosin, 41 kDa) [12] are muscular proteins. Ani s 4 (9 kDa) [13] and Ani s 6 (7 kDa) [14] are protease inhibitors.…”
Section: Introductionmentioning
confidence: 99%